Analisis Yuridis Daluwarsa Hak Waris atas Tanah dalam Perspektif Hukum Perdata Indonesia - Clarissa Gunawan; Elisabeth Julietha Roulina; Nayna Carissa Putri Ariefandi; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
: This study examines the expiration of inheritance rights over land within Indonesian civil law, where disputes often arise due to delays by heirs in asserting their rights while the land is controlled by other parties for a long period. This research aims to analyze the regulation of prescription and its application in judicial practice, particularly in Putusan Mahkamah Agung No. 6581 K/Pdt/2024. The study uses a normative juridical method with statutory and case approaches, supported by legal literature. The results show that prescription, as regulated in Article 1967 of the Indonesian Civil Code, serves as a legal mechanism to limit the time for filing claims in order to ensure legal certainty. In the examined case, the court rejected the heirs’ claim because the right to sue had expired due to prolonged control of the land by another party and the absence of legal action by the heirs. It is concluded that the application of prescription tends to prioritize legal certainty over the protection of inheritance rights, which may reduce the substantive rights of heirs